Assessment of priorities to 2010 for the poor and the environment - Thornton, Philip K.; Randolph, Thomas F.; Kristjanson, Patricia M.; Omamo, Steven Were; Odero, A.N.; Ryan, J.G. (International Livestock Research Institute, 2000)
This report describes the development and application of a quantitative priority assessment framework that allows the linking of agreed research priorities and resultant resource allocations. The five primary criteria by which priorities are assessed in the framework reflecting the vision , mission and mandate of ILRI and the priorities and strategies of the CGIAR are presented and discussed in this report. These are contribution to poverty reduction; expected economic impact using an economic surplus framework; environmental impact; internationality of the problem; and contribution to capacity building, development of new research tools, and improved research efficiency. Results of the priority assessment are discussed in relation to seven broad research and related areas.